Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kepuasan Kerja dan Kinerja Karyawan - Rizki Wahyuniardi; Sidik Nurjaman; Muhamad Rafi Ramadhan (Jurnal Optimasi Sistem Industri, 2018)
Perusahaan Listrik Negara (PLN) is a public company engaged in serving electricity in Indonesia. The company is a state-owned company which has a lot of human resources both from the level of general education up to the highest level of education. The rapid development of industrialization and technological innovation makes the company must be more competitive in facing the increasing of fierce competition in the current era of globalization. This study aims to analyze and prove the influence of organizational culture and work environment on employee performance through job satisfaction as a mediator or as an intervening variable. The study was conducted at PT. PLN (PERSERO) Distribution West Java Area Majalaya. Data were collected using questionnaires distributed to 146 employees and analyzed using Structural Equation Modeling (SEM) which was run by using AMOS 21.0 software. The results show that the organizational culture and work environment of PLN West Java Distribution Area Majalaya have a positive and significant influence on job satisfaction. Furthermore, the organizational culture, work environment, and job satisfaction of PLN employees have a positive influence on employee performance.